Cutaneous manifestation of COVID-19: What have we learned an year into the pandemic? - F. Sodeifian; S. Mushtaq; N. Rezaei (Elsevier, 2022)
Coronavirus disease-19 (COVID-19) is an emerging health situation caused by the "severe acute respiratory syndrome coronavirus 2" (SARS-CoV-2). The ongoing COVID-19 pandemic which emerged from the Chinese city of Wuhan in December 2019 has spread to over 188 countries and infected over 100 million people across the globe in over one year. Most common symptoms of COVID-19 include fever and respiratory illness. Among extrapulmonary signs associated with COVID-19, dermatological manifestations have been increasingly reported from different geographical regions. The exact incidence or prevalence of COVID-19 associated skin manifestation remains largely unknown and the pathophysiological mechanisms are still unclear. In this article, we have attempted to give a comprehensive overview of what has been learned an year into the pandemic on the epidemiology, clinical and histopathological features, pathophysiological mechanisms and clinical management of COVID-19 associated cutaneous manifestations. Resumen: La enfermedad por coronavirus de 2019 (COVID-19) es una situación sanitaria emergente causada por el "síndrome respiratorio agudo severo por coronavirus 2" (SARS-CoV-2). La pandemia por COVID-19 en curso, que surgió de la ciudad china de Wuhan en Diciembre de 2019, se ha propagado en 188 países, y ha infectado a más de 100 millones de personas a nivel mundial a lo largo de un año. Los síntomas más comunes de la COVID-19 incluyen fiebre y enfermedad respiratoria. Entre los signos extrapulmonares asociados a COVID-19 se han reportado cada vez más manifestaciones dermatológicas en las diferentes regiones geográficas. La incidencia o prevalencia exactas de las manifestaciones cutáneas asociadas a la COVID-19 son bastante desconocidas, y los mecanismos patofisiológicos siguen sin dilucidarse. En este artículo hemos tratado de aportar una visión general amplia de lo que hemos aprendido en un año de inmersión en la pandemia en cuanto a epidemiología y características clínicas e histopatológicas, mecanismos patofisiológicos y manejo clínico de las manifestaciones cutáneas asociadas a la COVID-19.